KOMUNIKASI INTERPERSONAL SEBAGAI STRATEGI PENINGKATAN PEMANGFAATAN LAYANAN PERPUSTAKAAN DI ERA DIGITAL - Muhamad Bisri Mustofa; Amelia Rosnaida; Siti Wuryan (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2023)
Technological advances that are happening today have had a significant impact and progress in various sectors, especially in the field of information and communication. Communication, in its various forms, is one of the aspects affected by these developments, including interpersonal communication. A close relationship between interpersonal communication and libraries can be found. The library, as a building, serves as a place where various activities related to managing, collecting, compiling, organizing, and processing library materials are carried out. Interpersonal communication plays an important role in the context of this library. This study applies qualitative methods in data collection by approaching literature review, namely "Interpersonal Communication as a Strategy for Increasing the Utilization of Library Services in the Digital Era". These data are obtained through online observations from websites that support data collection, from books and journals available. The purpose of this study was to understand the role played by interpersonal communication in service use strategies in libraries. In the application of interpersonal communication, librarians must have the following traits and attitudes. 1. Empathy 2. Support 3. Positive attitude 4. Equality or similarity 5. Openness. Interpersonal communication is used as a form of communication in this context. Interpersonal communication includes the interaction between communicators and communicants, either directly or through media or intermediaries. This type of communication is considered very effective in approaching, changing opinions, and human behavior as a strategy to increase the utilization of library services in the digital age.